Integration Of Environmental Safeguards Into Ethiopian Investment And Sectoral Laws - Ahmed, Mohammed Ibrahim (Journal of Sustainable Development Law and Policy, 2025)
The aim of this article is to analyse the nature, scope and extent to which environmental norms and principles are integrated into the Ethiopian investment laws. The integration of an environmental matter into investment laws is very important in that it ensures that investment bodies and institutions do not disregard the environment by focusing only on economic achievement. The legal analysis of Ethiopian investment laws shows that although they contain environmental protection provisions, the language, manner and extent of stipulation adopted differ. The Mining Operation Proclamation No. 678/ 2010, Energy Proclamation No. 810/2013 and Petroleum and Petroleum Products Supply Operation Proclamation No. 838/2014 integrate environmental protection in an unequivocal manner. However, the Investment Proclamation No. 769/2012 and Transaction of Precious Minerals Proclamation No. 651/2009 do not use similar language with proceeding proclamations. This article argues that if environmental protection is integrated both under the Investment Proclamation No. 769/2012 and the Transaction of Precious Minerals Proclamation No.651/2009, the language used in both proclamations should be unequivocal, clear and in good manner similar to those of Mining Operation Proclamation No. 678/2010, Energy Proclamation No. 810/2013 and Petroleum and Petroleum Products Supply Operation Proclamation No. 838/2014.